(untitled) (Ius Novum, 2021)
Internal control in public administration represents, on the one hand, numerous controls in the public sphere, and, at the same time, it constitutes an instrument for effective management in this sphere. The author presents the specificity of internal control in public administration, availing himself both of the theory of control and comparisons with internal control in the private sector and, for this purpose, he applies, in particular, the method of critical analysis of sources. In order to prove the impossibility of thoughtless application of provisions of the Act of 15 July 2011 on control in government administration to classical internal control, which is a specific style of self-control of an administrative body, the author compares, in different planes the activity of administrative bodies which act, on the one hand, as a controller, and, on the other hand, as the controlled, with the profile of internal control in which the controller and the controlled is the same body (unit). In this respect, the author uses, primarily, the dogmatic and legal method, characteristic of the exegesis of the complexity of the operation of government administration.